2004
DOI: 10.1212/01.wnl.0000125186.04867.34
|View full text |Cite
|
Sign up to set email alerts
|

The nature and course of neuropsychological morbidity in chronic temporal lobe epilepsy

Abstract: Neuropsychological morbidity in chronic temporal lobe epilepsy is widespread in nature despite a focal epileptic process. Cross-sectional analyses demonstrate that increasing duration of epilepsy is associated with worsening mental status. Individuals with less educational attainment (low cerebral reserve) exhibit especially poor cognitive function in association with chronicity of epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
191
1
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(211 citation statements)
references
References 43 publications
12
191
1
7
Order By: Relevance
“…As reviewed by Keller and Roberts (2008), VBM studies have found the largest effects in nearby ipsilateral medial temporal cortex, as well as more widespread effects in regions including the thalamus and frontal and parietal lobes. findings of more widespread alterations in cortical morphology that extend beyond the hippocampus are consistent with TLE's comorbid deficits in executive, intellectual and language functioning (Oyegbile et al, 2004). More recently, using methods that reconstruct the cortical surface to more precisely measure gray matter structure, researchers found up to 30% reductions in cortical thickness bilaterally in multiple frontal, temporal and occipital regions in TLE patients with MTS compared to controls (Lin et al, 2007;Bernhardt et al, 2010;Kemmotsu et al, 2011).…”
Section: Introductionmentioning
confidence: 87%
“…As reviewed by Keller and Roberts (2008), VBM studies have found the largest effects in nearby ipsilateral medial temporal cortex, as well as more widespread effects in regions including the thalamus and frontal and parietal lobes. findings of more widespread alterations in cortical morphology that extend beyond the hippocampus are consistent with TLE's comorbid deficits in executive, intellectual and language functioning (Oyegbile et al, 2004). More recently, using methods that reconstruct the cortical surface to more precisely measure gray matter structure, researchers found up to 30% reductions in cortical thickness bilaterally in multiple frontal, temporal and occipital regions in TLE patients with MTS compared to controls (Lin et al, 2007;Bernhardt et al, 2010;Kemmotsu et al, 2011).…”
Section: Introductionmentioning
confidence: 87%
“…It is generally acknowledged that memory functioning is the primary cognitive morbidity in TLE and is related to the functional adequacy of the hippocampus. Nevertheless, it is also evident that there is a more diffuse disruption of cognition in unilateral TLE (Glosser et al, 1997;Helmstaedter et al, 2003;Hermann et al, 1997) and that there is considerable heterogeneity in cognitive dysfunction among patients with unilateral TLE (Oyegbile et al, 2004). We have previously suggested that abnormalities outside the affected hippocampus and temporal lobe may contribute to nonmemory cognitive impairment (Hermann et al, 2003).…”
Section: Cognitive Functioningmentioning
confidence: 98%
“…Affected brain structures include temporal lobe structures adjacent and closely linked to the hippocampus such as the amygdala and entorhinal cortex (Bernasconi et al, 2005;Moran et al, 2001), as well as extratemporal lobe structures such as the thalamus and basal ganglia (Bonilha et al, 2005;Dreifuss et al, 2001;Natsume et al, 2003). Cognitive impairment in TLE has also been shown to encompass domains other than episodic memory, including intellectual functioning, language, executive functioning, visual perceptual functions, and motor abilities (Glosser et al, 1997;Hermann et al, 1997;Marques et al, 2007;Martin et al, 2000;Oyegbile et al, 2004). These findings raise the possibility that the broader pattern of cognitive impairment in TLE is associated with brain abnormalities in regions outside the temporal lobe.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive dysfunction is a common comorbidity in temporal lobe epilepsy (TLE) 1. Memory impairment is considered the characteristic cognitive feature of TLE 2, 3.…”
Section: Introductionmentioning
confidence: 99%